2012
DOI: 10.1021/cm203243x
|View full text |Cite
|
Sign up to set email alerts
|

Carbonophosphates: A New Family of Cathode Materials for Li-Ion Batteries Identified Computationally

Abstract: Identified Computationally. -A new class of materials which can intercalate lithium reversibly is discovered by a novel high-throughput ab initio computational approach. Na3FeCO3PO4 and Na3MnCO3PO4 are hydrothermally synthesized from aqueous solutions of FeSO4 or MnNO3, (NH4)2HPO4, and Na2CO3 (autoclave, 120°C, 70 h). Li-Na ion exchange produces Li 3 FeCO 3 PO 4 and Li 3 MnCO 3 PO 4 . The Mn carbonophosphate Li3MnCO3PO4 could potentially display a specific energy 45% greater than that of LiFePO4 and might be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
136
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(141 citation statements)
references
References 37 publications
5
136
0
Order By: Relevance
“…The aforementioned theoretical prediction and experimental investigations 13,[28][29][30] reveal clearly that Na 3 MnCO 3 PO 4 has a potential to be a high capacity cathode material for NIBs. Therefore, in this study, we have investigated factors, other than the electronic conductivity, that can affect the electrochemical properties of Na 3 MnCO 3 PO 4 as the cathode material for NIBs.…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…The aforementioned theoretical prediction and experimental investigations 13,[28][29][30] reveal clearly that Na 3 MnCO 3 PO 4 has a potential to be a high capacity cathode material for NIBs. Therefore, in this study, we have investigated factors, other than the electronic conductivity, that can affect the electrochemical properties of Na 3 MnCO 3 PO 4 as the cathode material for NIBs.…”
mentioning
confidence: 90%
“…13 Recently, our group has shown that high specific capacities, reaching as high as 92% of the theoretical, can be achieved when aided by the addition of 53 wt% (60 vol%) carbon black (CB) which provides a continuous CB network interacting with almost all Na 3 MnCO 3 PO 4 particles in the cathode and allow them to participate in electrochemical reactions. 30 The aforementioned theoretical prediction and experimental investigations 13,[28][29][30] reveal clearly that Na 3 MnCO 3 PO 4 has a potential to be a high capacity cathode material for NIBs. Therefore, in this study, we have investigated factors, other than the electronic conductivity, that can affect the electrochemical properties of Na 3 MnCO 3 PO 4 as the cathode material for NIBs.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Although this may appear much easier to conduct than experiments, the procedure still requires a significant amount of work: both the alkali-rich and the alkali-poor compositions have to be computed within a reasonable numerical accuracy for their energy difference to be meaningful, and sometimes with functionals that go beyond the usual local density approximation 8 or generalized gradient approximation 9,10 . While this is certainly tractable for a quite large set of compounds 5,11 , it becomes limited or prohibitive when realistic materials including defects, disorder or dopants must be studied 12,13 . Above all, first-principles calculations are not straightforwardly utilizable by non informed users.…”
mentioning
confidence: 99%